Respuesta :
Answer:
Option A is correct.
[tex]x = -6 \pm \sqrt{30}[/tex]
Explanation:
Given the expression: [tex]x^2+12x+6 = 0[/tex]
[tex]x^2+12x+6=0[/tex]
Subtract 6 from both sides, we get
[tex]x^2+12x=-6[/tex]
halve linear coefficient,then square it, and add it to both sides
[tex]x^2+12x+36=30[/tex]
Now, the left side is a perfect square
[tex](x+6)^2=30[/tex]
Now, take square root to both sides.
[tex]x+6=\sqrt{30}[/tex]
Subtract 6 from both sides, we get;
[tex]x = -6 \pm \sqrt{30}[/tex]
So, the solutions are : [tex]x = -6 \pm \sqrt{30}[/tex]
Answer:
The correct answer is A
[tex]x=-6\pm \sqrt{30}[/tex]
Step-by-step explanation:
The given expression is
[tex]x^2+12x+6=0[/tex]
Add [tex]-6[/tex] to both sides
[tex]x^2+12x=-6[/tex]
Add [tex](\frac{12}{2} )^2=(6)^2[/tex] to both sides.
[tex]x^2+12x+(6)^2=-6+(6)^2[/tex]
We got a perfect square on the left hand side
[tex](x+6)^2=-6+36[/tex]
Simplify the left hand side to get,
[tex](x+6)^2=30[/tex]
Take square root of both sides
[tex](x+6)=\pm \sqrt{30}[/tex]
Solve for [tex]x[/tex].
[tex]x=-6\pm \sqrt{30}[/tex]